Oligonucleotide microchips as genosensors for determinative and environmental studies in microbiology. - Guschin, D Y (1997)
The utility of parallel hybridization of environmental nucleic acids to many oligonucleotides immobilized in a matrix of polyacrylamide gel pads on a glass slide (oligonucleotide microchip) was evaluated. Oligonucleotides complementary to small-subunit rRNA sequences of selected microbial groups, encompassing key genera of nitrifying bacteria, were shown to selectively retain labeled target nucleic acid derived from either DNA or RNA forms of the target sequences. The utility of varying the probe concentration to normalize hybridization signals and the use of multicolor detection for simultaneous quantitation of multiple probe-target populations were demonstrated.